When and why do Austrian companies issue shares? - Johann Burgstaller (Johannes Kepler University of Linz, Department of Economics, 2005)
This paper examines the issuance of share capital via the Vienna Stock Exchange between 1985 and 2004. Evidence is supplied concerning the aggregate factors that explain the time-series variation in both the numbers of and proceeds from initial public offerings (IPOs) and seasoned equity offerings (SEOs). Results indicate that there is no cyclical sensitivity of issues, but that firms successfully time their offerings to take advantage of high stock market valuations and the associated low cost of equity capital. Corporate indebtedness and interest rates are significant determinants of SEOs in statistical and economic terms. The proceeds from IPOs, rather than funds raised by firms that are already listed, are used to finance subsequent investment.
Keywords: G18; G32; 330; Initial public offerings; seasoned equity offerings; corporate finance; capital structure; share issuance; going public; capital demand; stock market; cost of capital.; Aktiengesellschaft; Aktie; Wertpapieremission; Österreich